2019
DOI: 10.18203/issn.2454-5929.ijohns20192593
|View full text |Cite
|
Sign up to set email alerts
|

Complications of chronic suppurative otitis media and their management: five year study at tertiary care centre

Abstract: <p class="abstract"><strong>Background:</strong> Chronic suppurative otitis media is a disease that can end up in complications when treatment is delayed. The present prospective study was conducted at our tertiary care hospital and teaching centre to evaluate the incidence of complications of CSOM and their management.</p><p class="abstract"><strong>Methods:</strong> We analysed the clinical and intra operative findings, type of medical and surgical management and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This was in concordance with a study done by Basak et al where most of the patients were in the age group 21-30 years but in a study done by Mohite et al, most common age group was 35-55 years. 5,4 The male to female ratio was 1.27:1, which was similar to a study by Basak et al where the male: female ratio was 1.46. 5 It was also in concordance with to a study by Bento et al and Hussain et al 9,10…”
Section: Age and Gender Distributionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was in concordance with a study done by Basak et al where most of the patients were in the age group 21-30 years but in a study done by Mohite et al, most common age group was 35-55 years. 5,4 The male to female ratio was 1.27:1, which was similar to a study by Basak et al where the male: female ratio was 1.46. 5 It was also in concordance with to a study by Bento et al and Hussain et al 9,10…”
Section: Age and Gender Distributionsupporting
confidence: 89%
“…But life threatening complications are still seen to exist due to the changing virulence and susceptibility of bacteria, the state of individual patient and late presentation. 4 When water enters into ears or after an episode of upper respiratory tract infection, mostly patients present with painless otorrhoea, which resolves on medical management but recurrs again. So most of the cases suffer little due to discharge from ears, thereby delaying definitive management.…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Mohite a total 20 cases of CSOM were identified with complications, out of which 14 patients (70%) had EC while 06(30%) patients had IC complications. 5 The common complication in their study, in EC group was subperiosteal abscess-10, followed by Bezolds abscess-1, zygomatic abscess-1 and labyrinthitis-2. The complications encountered in IC group were temporal lobe abscess-1, pyogenic meningitis-2, lateral sinus thrombophlebitis-2 and extradural abscess-1.…”
Section: Types Of Complicationsmentioning
confidence: 89%